How does governance mediate links between ecosystem services and poverty alleviation? Results from a systematic mapping and thematic synthesis of literature. (October 2021) - Nunan, Fiona; Menton, Mary; McDermott, Constance L.; Huxham, Mark; Schreckenberg, Kate
Highlights: Little literature available that analyses how governance mediates links between ecosystem services and poverty alleviation. The literature that exists is dominated by forests, policy instruments and sub-Saharan Africa. Locally owned and inclusive governance increases the potential for ecosystem services to deliver on poverty alleviation. Co-existence of multiple governance systems make causality hard to trace, but creates opportunities as well as challenges. Suitable incentives are needed for governance to mediate positive links between ecosystem services and poverty alleviation. Abstract: Many efforts to improve the sustainable management of renewable natural resources in low- and middle-income countries seek to achieve 'win-win' outcomes – improved ecosystem health and improved livelihoods. Yet achieving such win–win outcomes is challenging, since many variables affect the potential for synergies. These variables include the quality and performance of governance. We conducted a systematic mapping of the literature and a thematic synthesis to identify how governance mediates relationships between ecosystem services and poverty alleviation. The systematic mapping focused on identifying which components of governance are studied and how much attention each geographic region and natural resource has received. We found that the literature is 'clumped', with some governance components, geographic areas and sectors studied well, and others poorly. The thematic synthesis drew on 191 papers and found very little literature that looked at the three areas of governance, ecosystem health/services and poverty alleviation/livelihoods together in detail, with little evidence of interdisciplinary investigation. Much of the research instead focuses on either governance itself or governance and livelihoods or governance and ecosystem health/services. Three key analytical themes were identified in response to the research question, which are that: locally owned and inclusive governance increases the potential for ecosystem services to deliver on improved livelihoods; there are often multiple governance structures and systems in place making causality difficult to trace, though such multiplicity creates opportunities for improved governance, ecosystem health and livelihoods as well as challenges; and, appropriate and adequate incentives are needed for governance to mediate positive links between ecosystem services and poverty alleviation.